Peningkatan kemampuan menganalisis perubahan wujud benda melalui penerapan model Scramble pada peserta didik kelas V sekolah dasar - Siska Tri Agustin (Universitas Sebelas Maret, 2019)
Abstract. The research purposed to describe the result of using scramble model in improving the analysis ability of material changes on students class V SD Negeri Triyagan 02 Sukoharjo Student Year 2018/2019. The form of this research was Classroom Action Research (CAR) was held for two cycle. Each cycle was conducted two meetings. Students class V SD Negeri Triyagan 02 Sukoharjo was the subject of this research. They were amounts 26 people. The data was collected by test, observation, interview, and documentary. All those datas was analysed by using interactive data analysis which was based on Miles and Huberman analysis for qualitative data. The result showed that: The score of analysis ability in material changes had improved after implementing scramble model in two cycles. The classical completeness just reached 7,69% and the grade average was 55,04 in pre-test. In first cycle, the classical completeness reached 42,31% and the grade average was 71,12. In second cycle, the classical completeness reached 80,77% and the grade average increased 80,92. Based on the result of this research, the researcher concluded that implementing scramble model proved increasing the analysis ability of material changes on students class V SD Negeri Triyagan 02 Sukoharjo Student Year 2018/2019.Keyword: the analysis ability, material changes, scramble model